Techno-economic versus energy optimization of natural gas liquefaction processes with different heat exchanger technologies. (15th April 2022) - Son, Heechang; Austbø, Bjørn; Gundersen, Truls; Hwang, Jihyun; Lim, Youngsub
Abstract: The energy intensity of the natural gas liquefaction process in LNG value chains is considerable, and therefore a number of energy optimization studies have been conducted to obtain optimal operating conditions and maximize process efficiency. In order to limit the size and cost of heat exchangers during energy optimization, a minimum temperature approach constraint is used for heat exchangers, primarily as an economic trade-off parameter. However, the cost optimal solution and appropriate values for the minimum temperature approach constraints depend on the process concept and the heat exchanger type. In this study, techno-economic optimization and energy optimization are performed for three different natural gas liquefaction processes and two different heat exchanger types with different unit cost and heat transfer performance. The results indicate that the techno-economic optimization can provide a better distribution of temperature driving forces in the heat exchangers and thereby lower total annualized cost irrespective of the minimum temperature approach constraint. The energy optimization performs better for low-efficiency processes than high-efficiency processes in terms of the total annualized cost. In addition, based on the techno-economic optimization results, appropriate values for the minimum temperature approach constraints as economic trade-off parameters in the energy optimization are investigated for the two heat exchanger types. Highlights: Energy optimization offers more economical results for low-efficiency processes. Techno-economic optimization provides superior results in terms of cost. A better distribution of temperature driving forces in heat exchangers is gained. Proper values of constraints for a minimum temperature approach are investigated.